2006
DOI: 10.1021/bc0600517
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of AP5346, a Novel Polymer-Linked Diaminocyclohexyl Platinum Chemotherapeutic Agent

Abstract: Syntheses of the novel polymer-bound platinum-based chemotherapeutic agent poly(HPMA)-GGG-Ama=Pt=(1R,2R)-DACH, AP5346, and its precursors are reported. The method utilized in preclinical development of AP5346 is described herein. Additionally, an improved synthesis, which has shown that ion exchange resins can be removed, significantly less platinum can be used when the reaction mixture is pH-stated, and the synthesis can be performed at a higher concentration, is reported. These combined improvements result i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
59
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(61 citation statements)
references
References 23 publications
2
59
0
Order By: Relevance
“…[32] Interestingly, the macromolecular platinum complexes AP5280 and AP5346 (ProLindac), [33,34] consist of a platinum diamine unit linked to a water-soluble copolymer N-(2-hydroxypropyl)methacrylamide (HPMA) through an amidomalonic acid as a (N,O) chelate, which slows the release of platinum species. Both conjugates reached phase I clinical trials (AP5346 started phase II in 2006), in which they demonstrated similar or better efficacy than carboplatin and oxaliplatin, with the added benefit of a higher therapeutic index (TI), due to the stability of the inactive prodrug conjugate in the systemic circulation.…”
Section: Biological Assaysmentioning
confidence: 99%
“…[32] Interestingly, the macromolecular platinum complexes AP5280 and AP5346 (ProLindac), [33,34] consist of a platinum diamine unit linked to a water-soluble copolymer N-(2-hydroxypropyl)methacrylamide (HPMA) through an amidomalonic acid as a (N,O) chelate, which slows the release of platinum species. Both conjugates reached phase I clinical trials (AP5346 started phase II in 2006), in which they demonstrated similar or better efficacy than carboplatin and oxaliplatin, with the added benefit of a higher therapeutic index (TI), due to the stability of the inactive prodrug conjugate in the systemic circulation.…”
Section: Biological Assaysmentioning
confidence: 99%
“…Platinum-based drugs have been used as frontline treatment for several cancers since the accidental discovery of the anticancer properties of cisplatin in the 1970s [59][60][61]. Since then, a new generation of platinum derivates, such as carboplatin, and new platinum-based agents (oxaliplatin, satraplatin and picoplatin) have contributed to improve their anticancer properties, time of tumor residence, and selectivity.…”
Section: Active Complexesmentioning
confidence: 99%
“…It has been reported that approximately 90% of patients treated with oxaliplatin suffered from acute neurotoxicity, while 10-15% of patients suffered from cumulative sensory. 10,11) Like other clinically available platinum anticancer drugs, oxaliplatin can not offer any substantial clinical advantages over the existing cisplatin, either. [12][13][14] Considering the advantages of oxaliplatin in treating ACRC and its drawbacks, we have been devoting to studying new platinum compounds with chiral ligands in recent years.…”
Section: Regular Articlementioning
confidence: 99%